2019
DOI: 10.1007/978-3-030-06067-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment Maneuvers and Higher PEEP, the So-Called Open Lung Concept, in Patients with ARDS

Abstract: The pathophysiology of ARDS and VILI The pathophysiology of ARDS is based on the triad of alveolar-capillary membrane injury, high-permeability (alveolar) edema and inflammation [10]. Histologically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Although a PEEP of 5 cmH 2 O in our study has been reported in a previous study, a higher PEEP may be much more beneficial for reducing atelectasis formation, as has been recommended by some researchers [41]. RM combined with PEEP was also beneficial for reducing atelectrauma [42], but it was only performed in OLV in our study. This may explain the high occurrence of atelectasis in the non-VATS group.…”
Section: Discussionsupporting
confidence: 48%
“…Although a PEEP of 5 cmH 2 O in our study has been reported in a previous study, a higher PEEP may be much more beneficial for reducing atelectasis formation, as has been recommended by some researchers [41]. RM combined with PEEP was also beneficial for reducing atelectrauma [42], but it was only performed in OLV in our study. This may explain the high occurrence of atelectasis in the non-VATS group.…”
Section: Discussionsupporting
confidence: 48%
“…[39][40][41] Although a PEEP of 5 cmH 2 O in our study has been reported in a previous study, a higher PEEP may be much more bene cial for reducing atelectasis formation, as has been recommended by some researchers. 42 RM combined with PEEP was also bene cial for reducing atelectrauma 43 , but it was only performed in OLV in our study. This may explain the high occurrence of atelectasis in the non-VATS group.…”
Section: Discussionmentioning
confidence: 78%
“…ARDS causes atelectasis, interfering with effective oxygenation and ventilation. The 'open lung concept' is a theoretical solution that relies on recruitment maneuvers to keep the lung open with PEEP while using low tidal volumes (Vt) to avoid barotrauma 27 . A common recommendation is ventilation with 6 mL/ kg-1 of the predicted body weight with a maximum plateau pressure (Pplat) of 30 cmH2O and a driving pressure of <15 cmH 2 O (figure 3) 28,29 .…”
Section: Mechanical Ventilation Strategies In Covid-19 Related Ardsmentioning
confidence: 99%